Dampak Pandemi Covid 19 Terhadap Sektor UMKM di Indonesia - Utami, Betty Silfia Ayu (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2021)
The COVID-19 pandemic has had a very significant impact on the domestic economy of nation-states and the existence of SME’s. This research aims to analyze the impact of the COVID-19 pandemic on the SME’s sector in Indonesia as well as the efforts made by the government in helping SME’S survive in the Covid-19 pandemic situation. The research method used in qualitative descriptive research, data collection techniques using documentation techniques, namely collecting data from various reference source. The results of the research are that the COVID-19 pandemic has had a tremendous impact on the performance of SME’s in Indonesia, this can be seen from the conditions before Covid-19, the percentage of good/very good business conditions of 92.7 percent and poor/very bad business conditions 1, 0 percent, after covid the bad/very bad business conditions increased by 56.8 percent compared to the original 1.0 percent. So it can be concluded that the COVID-19 pandemic has resulted in a decline in the performance of SME’s